Estimation of Diverse Porang (Amorphophallus Muelleri Blume) Age in Forest Are Based on Brancing Pattern of Leaf Petiolule - Harijati, Nunung; Mastuti, Retno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2014)
Porang is higher plant which has unique morphology. Tuber, petiole and lamina are the main part of its body. Even Porang doesn’t have true stem, only petiole, its lamina not simple leaves but compound leaves with special pattern. Branching patterns of petiolule are not same in different age. Therefore the aim of research was to observe branching pattern of petiolule from Porang age 1-4 that lived in their native habitat i.e. forest. The research was conducted in secondary forest in Sumberbendo village, Madiun. Determination porang age was helped by expert farmer that worked with porang for long time. The result showed that Porang age 1 had petiolule with braching type 1-0. Porang age 2 was 1-3, Porang age 3 was 1-3-2, and Porang age 4 was 1-3-2-2. The petiolule which acted as a base of new branch had one or few single simple leaf. The leave could be both sinus and un-sinus leaves located in between two initial or base branching. The position of the leaves were opposite or alternate along with petiolule. If location single leaf just in point branching, the new petiolule morphology was not be considered as petiolule but midrib.